In vitro screening for antioxidant and antimicrobial properties of five commercial Origanum species from Turkey - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2017)
The present study was conducted to evaluate the antioxidant and antimicrobial properties of methanol extracts of the five Origanum species, which are commercial importance in Turkey. Antioxidant activity was measured employing three methods namely, DPPH free radical scavenging activity, ABTS(+) radical cation scavenging activity and ferric reducing antioxidant/power activity, including total phenolic and total flavonoid contents. In addition, antimicrobial activities of methanol extracts from five Origanum species aerial parts were investigated against Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus mirabilis and Candida albicans test organisms using the disk diffusion and microdilution methods. Antioxidant studies suggested that methanol extracts behaved as a strong DPPH free radical, ABTS radical cation scavenging activity and ferric reducing antioxidant/power activity. The antimicrobial test results showed that the methanol extracts of all Origanum species had great potential of antibacterial activity against Staphylococcus aureus. As a conclusion of this study, the methanol extracts of five Origanum species showed strong antioxidant and antibacterial activity and therefore, they can be used as a natural preservative ingredient in food and/or pharmaceutical industry.
Keywords: Origanum species; Antioxidant; Antimicrobial; ESSENTIAL OIL; CHEMICAL-COMPOSITION; ONITES LAMIACEAE; L. EXTRACTS; OREGANO; ANTICANCER; CAPACITY; SYRIACUM; BEVANII; PLANT